Thermal equilibrium responses in Guzerat cattle raised under tropical conditions - Camerro, Leandro Zuccherato [UNESP]; Campos Maia, Alex Sandro [UNESP]; Chiquitelli Neto, Marcos [UNESP]; Melo Costa, Cintia Carol de [UNESP]; Castro, Patric Andre [UNESP] (Elsevier B.V., 2016)
The literature is very sparse regarding research on the thermal equilibrium in Guzerat cattle (Bos indicus) under field conditions. Some factors can modify the physiological response of Guzerat cattle, such as the reactivity of these animals to handling. Thus, the development of a methodology to condition and select Guzerat cattle to acclimate them to the routine collection of data without altering their physiological response was the objective of the preliminary experiment. Furthermore, the animals selected were used in the main experiment to determine their thermal equilibrium according to the thermal environment. For this proposal, the metabolic heat production and heat exchange between the animal and the environment were measured simultaneously in the field with an indirect calorimetry system coupled to a facial mask. The results of the preliminary experiment showed that the respiratory rate could demonstrate that conditioning efficiently reduced the reactivity of the animals to experimental handling. Furthermore, the respiratory rate can be used to select animals with less reactivity. The results of the main experiment demonstrate that the skin, hair-coat surface and expired air temperature depend on the air temperature, whereas the rectal temperature depends on the time of day; consequently, the sensible heat flow was substantially reduced from 70 to 20 when the air temperature increased from 24 to 34 degrees C. However, the respiratory latent heat flow increased from 10 to 15 W m(-2) with the same temperature increase. Furthermore, the metabolic heat production remained stable, independent of the variation of the air temperature; however, it was higher in males than in females (by approximately 25%). This fact can be explained by the variation of the ventilation rate, which had a mean value of 1.6 and 2.2 L s(-1) for females and males, respectively. (V) 2016 Elsevier Ltd. All rights reserved.
Keywords: Indirect calorimetry; Thermal equilibrium; Thermoregulation